Pengaruh Teknik Blending terhadap Karakteristik Kimia dan Sensori Kopi Arabika (Coffea Arabica L.) - Kusumaningtyas, Rizky Nirmala; Arifin, Trisna Levia; Setyoko, Ujang; Rosdiana, Eva; Alwi, Annisa Lutfi; Pratita, Dian Galuh (Food Scientia: Journal of Food Science and Technology, 2025)
Post-harvest coffee processing methods are primarily classified into two categories: dry (natural) and full-washed processing, which significantly impact the sensory profile of the coffee. Different techniques create unique flavors, influencing consumer preferences and coffee quality. To enhance the quality and market value of coffee, blending practices are utilized. Blending practices combine various coffee types to achieve the desired flavor profiles, as the choice of beans and the blending formulation significantly impact the taste and aroma. A suboptimal blending formulation can potentially undermine the coffee product's overall taste quality. This study is designed to investigate the impact of Arabica coffee's blending ratio derived from natural and full-washed processing on both chemical and sensory characteristics. The methodology employed is a non-factorial completely randomized design featuring a blending formulation ratio factor representing the percentage of roasted beans from natural to full-washed processing. The blending ratios considered are as follows: P1 = 80:20; P2 = 70:30; P3 = 60:40; P4 = 40:60; P5 = 30:70; and P6 = 20:80. This research was conducted with four replications, resulting in a total of 24 experimental units. The parameters evaluated in this coffee blending study include Total Dissolved Solids (TDS), pH, moisture content, and sensory attributes (aroma, color, flavor, acidity, and overall acceptability). The results indicate that the blending ratio of roasted beans from different coffee processing methods has a statistically significant effect (α = 0.05) on the chemical and sensory characteristics of the blended coffee produced.